Risk - Lupton, Deborah 1963- (Routledge, 2024)
"We are living in a world in which the existence of risk is constantly debated, misinformation and disinformation are rife and spread quickly and easily through online media, and where governments and institutions continue to avoid taking decisive action even when there is general agreement that a serious threat exists. Understanding how people, social groups and social organizations understand, respond to and act on threats, hazards and dangers is more important than ever. In Risk, Lupton asserts the ongoing importance of the analysis of risk in our age of permacrisis and mounting scepticism about experts and science, and calls for a 're-turn' to risk theory in the social sciences. This fully revised and expanded new edition of the influential text includes a new chapter on risk information and denial in the context of the climate crisis and the COVID-19 pandemic. The book outlines the three major approaches to risk in social and cultural theory, devoting a chapter to each.
Keywords: Soziologie; Risikotheorie; Risiko; Risk / Sociological aspects; Risk perception / Social aspects